Impact of social trust, social networks, and financial knowledge on financial well-being of micro-entrepreneurs in Malaysia and Indonesia - Nisful Laila; Shafinar Ismail; Putri Aliah Mohd Hidzir; Ririn Tri Ratnasari; Nurul Ezaili Alias (Cogent Business & Management)
Post-crisis, micro-entrepreneurs struggle to revive their businesses impacted by the global economic downturn. As businesses shut down, many have also chosen to dive into informal sectors to replace their lost sources of income. This study examined the influence of social trust, social networks, and financial knowledge on the financial well-being of micro-entrepreneurs in Malaysia and Indonesia. This study’s framework is underpinned by social capital theory. Questionnaires were distributed in both countries through purposive sampling, and 330 valid respondents were included in the analysis using Partial Least Square Structural Equation Modelling (PLS-SEM). The results revealed that all variables significantly impacted the financial well-being of micro-entrepreneurs, with financial knowledge being the strongest predictor. This study contributes to the literature by incorporating elements of social capital towards assess financial well-being through a multigroup analysis of neighbouring countries. The results may also help policymakers and financial institutions construct better offerings and services for underserved communities, especially for micro-entrepreneurs.